Propuesta didáctica para resolución de problemas de física por investigación dirigida: un enfoque para fomentar la cultura científica en estudiantes de grado décimo del Instituto Técnico Rafael Reyes - Vega Pinzón, Adriana del Pilar (Revista Científica, 2011)
The objective of this research work is to indentify an assess how the planning, implementation and evaluation of a didactic proposal physics problem resolutions for research conducted, in the thematic unity of kinematics, enables the promotion of the scientific culture in students implementation and evaluation of a didactic proposal physics problem resolutions for research conducted, in the thematic unity of kinematics, enables the promotion of the scientific culture in students of tenth grade of Instituto Tecnico Rafael Reyes. he implementation of the proposal has been made for two years, involving about 120 students in tenth grade in the course of Physics for the years 2009, 2010 and 2011. The design that was used is pre-post, before and after the explosion to the experimental intervention, based on the measurement and comparison of attitudes toward physical science and scientific work, learning with understanding and the ability to solve problems in students.The obtained results show the validity of the hypothesis, showing that with the implementation of the teaching model for directed research are overcome many deficiencies of the traditional education intermsof failure and the scientificcultureisfomentedin terms of improvement of motivation, interest, significant learning and problem solving in the course of physics.